ENHANCEMENT OF THE CONVECTIVE COOLING OF TWO HEATERS IN A RECTANGULAR DUCT BY IMPINGING JETS - Marchi Neto, I.; Altemani, C. A. C. (Revista de Engenharia Térmica, 2014)
A numerical investigation was performed to compare two alternative configurations for the convective air cooling of two heaters flush mounted on the lower horizontal wall of a rectangular duct. One configuration consisted of duct flow with uniform airflow velocity and temperature at the duct inlet and the heaters were located in the flow entrance region. In the other, the cooling was obtained by impinging air jets exiting with uniform velocity and temperature from two square holes on the upper duct wall just above the heaters. The simulations were performed under steady state conditions considering the three dimensional flow region of each configuration, where the conservation equations were solved. The results were presented in the form of the adiabatic Nusselt number and a dimensionless pressure drop for both configurations, in the range of the duct Reynolds number from 500 to 9,000.